Interpretating English Terminology in Social and Political Aspects of the Society - Doniyorova Gulruh Shoniyozovna (International Journal on Integrated Education, 2022)
Many linguists point out that a socio-political translation does not need a kind of intelligence from them in comparison to a specific translation, for instance, where it is required to have information in the special area of translated field.. However, background information has an important place in socio-political translation, and the more extensive this information, the more adequate the final outcome. Engaging socio-political translation requires considering and discussing specific features and, of course, a high lexical degree, since the vocabulary of the socio-political area is most susceptible to semantic changes. The equivalence of the translation means that the translator must design speech works in the target language that are amounting to the translated speech works according to the criteria.